Understanding social media advertising effect on consumers' responses: An empirical investigation of tourism advertising on Facebook. Issue 3 (9th April 2018) - Hamouda, Manel
Abstract : Purpose: This study aims to deepen the current understanding of social media advertising by using the Ducoffe's advertising value model. The purpose of this paper is to examine the antecedents of advertising value and its consequences on consumers' attitude and behavior in the specific context of tourism advertising on Facebook. Design/methodology/approach: Survey was conducted on a quota sample of 352 Tunisian Facebook users. Web-based questionnaires were used to collect the data which was analyzed using exploratory factor analysis and structural equation modeling. Findings: Findings indicate that there is a significant relationship between informativeness, entertainment, credibility and social media advertising value. This positive value will affect favorably consumers' attitude toward social media advertising and their behavioral responses. The moderator effect of corporate reputation was also confirmed in this relationship. Practical implications: Tourism marketers should focus not only on developing information-rich and entertaining social media advertisements but also a credible content of the ads. Furthermore, Facebook should be systematically integrated by tourism practitioners in their communication strategy as it affects the attitude and consequently the behavior of the consumers especially when the company using social media advertising has a good corporate reputation. Originality/value: In the tourism context, the effectiveness of social media advertising remains little known to practitioners and scholars despite the frequent use of social media by tourism customers and companies in recent years. So, this research study contributes to a better understanding of the use of social media advertising on Facebook regarding tourism products and services.